Morphological variation in Leptodactylus lutzi (Anura, Leptodactylidae) with description of its advertisement call and notes on its courtship behavior - Kok, Philippe J. R.; Kokubum, Marcelo N. C.; MacCulloch, Ross D.; Lathrop, Amy (Phyllomedusa: Journal of Herpetology, 2007)
Prior to this study, Leptodactylus lutzi was known only from three localities in west-central Guyana. We refer here to a series of 60 additional specimens of L. lutzi collected in Kaieteur National Park, Mount Ayanganna, Mount Wokomung and the Merume Mountains in the Pakaraima Mountains region, substantially extending the known distribution of the species. We provide a revised diagnosis and an expanded description of L. lutzi discussing the extent of color-pattern variation in the species. Additionally, we describe its advertisement call and provide data on its reproductive biology.